Penerapan Model Pembelajaran Langsung melalui Metode Permainan matematika pada Pembelajaran Matematika Materi Bilangan Berpangkat - Jonly H. Rondonuwu; Jorry F. Monoarfa; Derel F. Kaunang (Departement of Mathematics Education, 2023)
The purpose of this study was to determine whether using the Direct Learning Model Through the Mathematical Game Method could exceed the KKM value determined by the school, namely 70. The population in this study was all students of class IX SMP Negeri 4 Suluun Tareran and the sample in this study was IX SMP Negeri 4 Suluun Tareran. The design of this research is One-Shoot Case Study. Data obtained from student learning outcomes test, namely the final test (posttest). After the data was obtained, a normality test was performed using the Liliefors test. From the test, it was obtained that and Because the posttest scores in class IX are normally distributed. Then, a hypothesis test was carried out using a t-test with a significance level of 0,05, the results obtained were dan , then so reject and accept which is the result of learning using direct learning models through the method of math games on the material. A number with a rank greater than the KKM value determined by the school is 70, with an average learning outcome of 77.52 which is greater than the KKM score.